Aramid fiber composite modified waterborne epoxy coating and a preparation method thereof
Patent Information
- Application Number
- CN202411082510.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-08
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2044-08-08
AI Technical Summary
但芳纶纤维化学稳定性好,不易与其他介质相互作用,容易导致在涂料中团聚,无法均匀分散,造成乳液颗粒之间存在间隙,进而导致腐蚀介质会沿间隙渗透进涂层内部,降低了涂层的防腐效果
[0029]本发明采用芳纶纤维对水性环氧涂料进行改性,有效增强了涂层的防腐蚀和耐盐雾性能,芳纶纤维作为一种增强材料,能填充涂层因水分蒸发固化成膜后出现的针孔和缺陷,屏蔽腐蚀介质的进入,其次由于芳纶纤维多层的包覆,外界的腐蚀介质需要更长的时间穿过芳纶纤维的保护膜,增大了腐蚀液渗透到金属基材表面的难度。芳纶纤维主要为对位芳纶纤维和间位芳纶纤维,对位芳纶纤维具有高强高模、耐高温、耐腐蚀的特点,其比表面积大、表面能高、分散性好、保水率,阻燃性能优异。此外,芳纶纳米纤维成膜之谜,尺寸稳定性好,绝缘性好,能与水形成均匀的悬浊液,易于喷涂。
Smart Images

Figure CN118931323B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of anti-corrosion coatings technology, and in particular to an aramid fiber composite modified waterborne epoxy coating and its preparation method. Background Technology
[0002] Because steel is susceptible to oxidation and corrosion, applying anti-corrosion coatings to its surface is a widely used and highly effective protective technique. In recent years, environmentally friendly waterborne epoxy polymer anti-corrosion coatings have emerged. However, during application, pinholes and defects inevitably appear in waterborne coatings after the water evaporates and solidifies into a film. These defects can easily allow corrosive media such as water molecules, oxygen molecules, and chloride ions to penetrate the environment, causing the steel to rust. Therefore, adding various synergistic materials to waterborne coatings is crucial for improving their long-term anti-corrosion performance.
[0003] Among various enhancement materials, aramid fibers stand out due to their good chemical corrosion resistance, high specific strength and specific modulus, and low specific density. Moreover, fibrous aramid can fill the pinholes and defects formed by the coating, shield the penetration of corrosive media, and form a dense passivation layer on the surface of the metal substrate.
[0004] Currently published methods for preparing aramid fiber-reinforced waterborne epoxy anticorrosive coatings, such as CN106336775A, typically involve directly adding aramid fibers to a container and grinding them with the pigments and fillers in the coating. However, aramid fibers have good chemical stability and do not easily interact with other media, which can lead to agglomeration in the coating and uneven dispersion. This creates gaps between emulsion particles, allowing corrosive media to penetrate into the coating and reduce its anticorrosive effect. Summary of the Invention
[0005] To address the problems of existing technologies, this invention provides an aramid fiber composite modified waterborne epoxy coating and its preparation method. First, aramid fibers are dispersed in an aqueous phase under the action of a dispersant and high shear force. Next, an emulsifier, epoxy resin, and co-solvent are heated to melt, and dispersion is initiated. A pre-dispersed aramid fiber aqueous solution is then added dropwise using a peristaltic pump. During the phase rotation process, the aramid fibers are uniformly coated on the surface of the emulsion particles, thus completing the dispersion of the aramid fibers in the epoxy emulsion and preventing agglomeration. Using this method, the aramid fibers can effectively fill pinholes and defects that appear after water evaporation and curing into a film, reducing the gaps between emulsion particles and improving the coating's water vapor shielding performance, salt spray resistance, and corrosion resistance.
[0006] To achieve the above objectives, the present invention adopts the following technical solution:
[0007] A waterborne epoxy coating modified with aramid fiber composite, comprising two components, A and B, wherein component A, by weight, includes 40-60 parts of aramid fiber modified epoxy emulsion, 10-70 parts of pigments and fillers, 0.1-3 parts of flash rust inhibitor, 0.1-5 parts of dispersant, 2-3 parts of film-forming aid, 1-3 parts of defoamer, 1-3 parts of thickener, 1-2 parts of wetting agent, and 10-50 parts of water; wherein component B, by weight, includes 10-40 parts of curing agent and 5-20 parts of propylene glycol methyl ether; the mass ratio of components A and B is 100:30-40.
[0008] The aramid fiber-modified epoxy emulsion was prepared according to the following method:
[0009] (1) Add 1-10 parts of aramid fiber, 0.1-1 parts of dispersant, and 50-90 parts of water to the jacketed reactor, turn on the condenser, and disperse at 25℃ and 2000-4500r / min for 2-6 hours to obtain a well dispersed aramid fiber aqueous solution.
[0010] (2) Add 40-60 parts of epoxy resin, 4-8 parts of emulsifier, and 6-12 parts of cosolvent to the jacketed reactor. Heat to 60-80℃ until melted, then start the dispersion and stir evenly at 1000-2000r / min. Keep the material temperature at 60-65℃, turn on the peristaltic pump, and add 30-60 parts of aramid fiber aqueous solution at a rate of 1-2ml / min. After the addition is complete, stir at 1000-1500r / min for 15-30min. After filtration, the aramid fiber modified epoxy emulsion is obtained.
[0011] This invention further provides a method for preparing the above-mentioned aramid fiber composite modified waterborne epoxy coating, the specific steps of which include:
[0012] S1: Preparation of component A: Add aramid fiber modified epoxy emulsion, pigments and fillers, anti-flash rust agent, dispersant, film-forming aid, defoamer, thickener, wetting agent and water to the reactor according to the formula, grind until the fineness is less than 25μm, filter and discharge to obtain component A;
[0013] S2: Preparation of component B: Add curing agent and propylene glycol methyl ether to the reactor according to the ratio, stir and mix evenly at a speed of 500-1000 rpm / min, filter and discharge to obtain component B;
[0014] S3: Mix component A and component B at a mass ratio of 100:30-40, stir until homogeneous, and filter to obtain a waterborne epoxy coating modified with aramid fiber composite.
[0015] Preferably, the epoxy resin is selected from bisphenol A type epoxy resin; more preferably, it is selected from one or more of E51, E44, and E20 epoxy resins.
[0016] Preferably, the aramid fiber is a para-aramid fiber; more preferably, the aramid fiber has a diameter between 10-100 nm and an aspect ratio of about 3000.
[0017] Preferably, the emulsifier is a nonionic emulsifier of polyetheramine grafted modified epoxy resin, and the preparation method is as follows:
[0018] Weigh out 2-5 parts by weight of E51 epoxy resin, 1-5 parts by weight of polyethylene glycol with a molecular weight of 3500-6000, 0.5-2 parts by weight of polyetheramine with a molecular weight of 2000-4000, and 0.01-0.03 parts by weight of tetrafluoroboric acid. Add the E51 epoxy resin and polyethylene glycol to the reactor, heat to 100-110℃, add all the tetrafluoroboric acid dropwise over 1-2 hours, keep the reaction at 100-110℃ for 3-4 hours, add the polyetheramine, heat to 120-140℃, and continue the reaction for 4-6 hours to obtain a nonionic emulsifier for polyetheramine grafted modified epoxy resin.
[0019] Preferably, the co-solvent is selected from one or more of propylene glycol methyl ether, propylene glycol butyl ether, and acetone.
[0020] Preferably, the pigments and fillers are selected from one or more of titanium dioxide, talc, barium sulfate, iron oxide red, zinc phosphate, strontium chrome yellow, and mica powder.
[0021] Preferably, the dispersant is selected from one or more of dodecyl sulfonates, alkyl alcohol polyoxyethylene ethers, polyacrylates, and polycarboxylates.
[0022] Preferably, the film-forming aid is selected from one or more of dipropylene glycol methyl ether, propylene glycol methyl ether, and dipropylene glycol butyl ether.
[0023] Preferably, the defoamer is selected from one or more of polyether block defoamers, organosilicon defoamers, and mineral oil defoamers.
[0024] Preferably, the thickener is selected from one or more of cellulose-based, polyacrylic-based, inorganic thickeners, and polyurethane-based thickeners.
[0025] Preferably, the curing agent is selected from one or more of Huntsman 3986, Hansen 6870, and Zhanxin 613W.
[0026] No special selection is required for the anti-flash rust agent; it can be prepared or purchased using existing technology. Preferably, it can be one or more of CK-20, CK-35, and HY-72.
[0027] The wetting agent is not specifically selected and can be prepared or purchased using existing technology. Preferably, it can be one or more of TEGO-245, TEGO-270, and TEGO280.
[0028] The beneficial effects of this invention are:
[0029] This invention utilizes aramid fibers to modify waterborne epoxy coatings, effectively enhancing the coating's corrosion resistance and salt spray resistance. As a reinforcing material, aramid fibers can fill pinholes and defects that appear after the coating cures due to moisture evaporation, shielding it from corrosive media. Furthermore, due to the multi-layered coating of aramid fibers, external corrosive media require a longer time to penetrate the protective film, increasing the difficulty of corrosive liquids penetrating the metal substrate surface. The aramid fibers are mainly para-aramid and meta-aramid fibers. Para-aramid fibers possess high strength, high modulus, high temperature resistance, and corrosion resistance, along with a large specific surface area, high surface energy, good dispersibility, high water retention, and excellent flame retardant properties. In addition, aramid nanofibers exhibit excellent film-forming properties, good dimensional stability, good insulation, and the ability to form a uniform suspension with water, making them easy to spray.
[0030] This invention utilizes high-speed shear force to disperse aramid fibers in an aqueous phase beforehand. During the phase inversion process, as the system transforms from oil-in-water to water-in-oil, the aramid fibers more uniformly encapsulate the emulsion particles, thus completing the dispersion of aramid fibers in the aqueous epoxy emulsion and preventing agglomeration.
[0031] The present invention employs a relatively simple process and principle, is highly operable, environmentally friendly, pollution-free, and highly repeatable, and can realize large-scale industrial continuous production.
[0032] The present invention preferably uses a special emulsifier, which is prepared by grafting epoxy resin with polyetheramine. It retains epoxy groups and has good compatibility with epoxy resin. In the later stage of emulsion curing and film formation, it can participate in curing and film formation, further improving the crosslinking density of the coating.
[0033] This invention limits the amount of aramid fiber added in the preparation method. When the amount added is too low, it is insufficient to fill the defects generated during the subsequent curing of the water-based coating, resulting in limited improvement on the anti-corrosion performance of the water-based epoxy coating. When the amount added is too high, the excessive aramid fiber is difficult to disperse, and the excess aramid fiber will always remain outside the system, causing certain damage to the performance of the coating. Attached Figure Description
[0034] Figure 1 This is the aqueous solution of well-dispersed aramid fibers from Example 2;
[0035] Figure 2 Fourier transform infrared image of the emulsifier for polyetheramine-grafted epoxy resin;
[0036] Figure 3 This is a TEM image of the aramid fiber aqueous solution in Example 2;
[0037] Figure 4This is a TEM image of the aramid fiber modified epoxy emulsion in Example 2;
[0038] Figure 5 This is a comparison chart of the salt spray resistance results of Comparative Example 1 and Example 2. Detailed Implementation
[0039] To enable those skilled in the art to better understand the technical solutions of this invention, the technical solutions in the embodiments of this invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of this invention, and not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort should fall within the scope of protection of this invention.
[0040] The para-aramid fiber is produced by Shandong Jufang New Material Co., Ltd., with a diameter between 10-100nm and an aspect ratio of about 3000.
[0041] Example 1
[0042] Preparation of emulsifiers:
[0043] Weigh out 2 parts of E51 epoxy resin, 1 part of 4000 molecular weight polyethylene glycol, 0.5 parts of 3000 molecular weight polyetheramine, and 0.01 parts of tetrafluoroboric acid. Add the E51 epoxy resin and polyethylene glycol to the reactor, heat to 100℃, add all the tetrafluoroboric acid dropwise over 1 hour, keep the reaction at 100℃ for 3 hours, add the polyetheramine, heat to 120℃, and continue the reaction for 4 hours to obtain a nonionic emulsifier for polyetheramine grafted modified epoxy resin.
[0044] Preparation of aramid fiber modified epoxy emulsion:
[0045] (1) Weigh 2 parts of aramid fiber, 50 parts of water, and 0.2 parts of dispersant by weight, turn on the cooling water, and disperse at 3000 r / min for 4 h at 25℃ to obtain a well dispersed aqueous solution of aramid fiber, wherein the aramid fiber is para-aramid fiber.
[0046] (2) By weight, add 50 parts of E20 epoxy resin, 5 parts of emulsifier and 8.5 parts of cosolvent to the jacketed reactor. Heat to 80°C until melted, then start the dispersion and stir at 1500 r / min until uniform. Keep the material temperature at 60°C, turn on the peristaltic pump and add 46.5 parts of aramid fiber aqueous solution at 2 ml / min. After the addition is complete, stir at 1500 r / min for 30 min. After filtration, the aramid fiber modified epoxy emulsion is obtained.
[0047] Preparation of aramid fiber composite modified waterborne epoxy coatings:
[0048] The amounts of each component by weight are shown in the table below. Accurately weigh component 1 and add it to the dispersion tank. Add components 2-5 sequentially while stirring, and disperse at 1000 rpm for 5 minutes. Add components 6-14 sequentially while stirring, and disperse at 1000 rpm for 10 minutes. Then add zirconium beads and grind at high speed until the fineness is less than 25 microns. Filter and set aside to obtain component A. Accurately weigh components 15 and 16, mix and stir evenly, and filter to obtain component B. Mix components A and B at a mass ratio of 100:32, stir evenly, and filter to obtain an aramid fiber composite modified waterborne epoxy coating.
[0049] 1 water 18.0 2 Propylene glycol methyl ether 2.0 3 Dispersant TEGO 760W 1.2 4 TEGO 270 wetting agent 0.2 5 Defoamer TEGO 810 0.1 6 Titanium dioxide 10.3 7 Iron Red 0.8 8 Zinc phosphate 4.0 9 mica powder 3.0 10 talcum powder 7.0 11 Barium sulfate 10.0 12 aramid fiber modified epoxy emulsion 40.0 13 Thickener TEGO 3060 1.3 14 CK-20 anti-flash rust agent 2.1 15 Hardener 3986 16.0 16 Propylene glycol methyl ether 16.0
[0050] Example 2
[0051] Preparation of emulsifiers:
[0052] Weigh out 2 parts of E51 epoxy resin, 2 parts of 4000 molecular weight polyethylene glycol, 1 part of 2000 molecular weight polyetheramine, and 0.02 parts of tetrafluoroboric acid. Add the E51 epoxy resin and polyethylene glycol to the reactor, heat to 100℃, add all the tetrafluoroboric acid dropwise over 1 hour, keep the reaction at 100℃ for 3 hours, add the polyetheramine, heat to 120℃, and continue the reaction for 4 hours to obtain a nonionic emulsifier for polyetheramine grafted modified epoxy resin.
[0053] Preparation of aramid fiber modified epoxy emulsion:
[0054] (1) Weigh 4 parts of aramid fiber, 50 parts of water, and 0.4 parts of dispersant by weight, turn on the cooling water, and disperse at 3000 r / min for 4 h at 25℃ to obtain a well dispersed aqueous solution of aramid fiber, wherein the aramid fiber is para-aramid fiber.
[0055] (2) By weight, add 55 parts of E20 epoxy resin, 6 parts of emulsifier and 9 parts of cosolvent to the jacketed reactor. After heating to melt at 80°C, start the dispersion and stir evenly at 1500 r / min. Keep the material temperature at 60°C. Start the peristaltic pump and add 45 parts of aramid fiber aqueous solution at a rate of 2 ml / min. After the addition is complete, stir at 1500 r / min for 30 min. After filtration, the aramid fiber modified epoxy emulsion is obtained.
[0056] Preparation of aramid fiber composite modified waterborne epoxy coatings:
[0057] The amounts of each component by weight are shown in the table below. Accurately weigh component 1 and add it to the dispersion tank. Add components 2-5 in sequence while stirring, and disperse at 1000 rpm for 5 minutes. Add components 6-14 in sequence while stirring, and disperse at 1000 rpm for 10 minutes. Then add zirconium beads and grind at high speed until the fineness is less than 25 microns. Filter and set aside to obtain component A. Accurately weigh components 15 and 16, mix and stir evenly, and filter to obtain component B. Mix components A and B at a mass ratio of 100:32, stir evenly, and filter to obtain an aramid fiber composite modified waterborne epoxy coating.
[0058] 1 water 18.0 2 Propylene glycol methyl ether 2.0 3 Dispersant TEGO 760W 1.2 4 TEGO 270 wetting agent 0.2 5 Defoamer TEGO 810 0.1 6 Titanium dioxide 10.3 7 Iron Red 0.8 8 Zinc phosphate 4.0 9 mica powder 3.0 10 talcum powder 7.0 11 Barium sulfate 10.0 12 aramid fiber modified epoxy emulsion 40.0 13 Thickener TEGO 3060 1.3 14 CK-20 anti-flash rust agent 2.1 15 Hardener 3986 16.0 16 Propylene glycol methyl ether 16.0
[0059] Example 3
[0060] Preparation of emulsifiers:
[0061] Weigh out 2 parts of E51 epoxy resin, 1 part of 6000 molecular weight polyethylene glycol, 0.5 parts of 2000 molecular weight polyetheramine, and 0.01 parts of tetrafluoroboric acid; add E51 epoxy resin and polyethylene glycol to a reactor, heat to 100℃, add all the tetrafluoroboric acid dropwise over 1 hour, keep the reaction at 100℃ for 3 hours, add polyetheramine, heat to 120℃, and continue the reaction for 4 hours to obtain a nonionic emulsifier for polyetheramine grafted modified epoxy resin.
[0062] Preparation of aramid fiber modified epoxy emulsion:
[0063] (1) Weigh 6 parts of aramid fiber, 50 parts of water, and 0.6 parts of dispersant by weight, turn on the cooling water, and disperse at 3000 r / min for 4 h at 25℃ to obtain a well dispersed aqueous solution of aramid fiber, wherein the aramid fiber is para-aramid fiber.
[0064] (2) By weight, add 50 parts of E20 epoxy resin, 5 parts of emulsifier and 8.5 parts of cosolvent to the jacketed reactor. Heat at 80°C until melted, then start the dispersion and stir at 1500 r / min until uniform. Keep the material temperature at 60°C, turn on the peristaltic pump and add 46.5 parts of aramid fiber aqueous solution at 2 ml / min. After the addition is complete, stir at 1500 r / min for 30 min. After filtration, the aramid fiber modified epoxy emulsion is obtained.
[0065] Preparation of aramid fiber composite modified waterborne epoxy coatings:
[0066] The amounts of each component by weight are shown in the table below. Accurately weigh component 1 and add it to the dispersion tank. Add components 2-5 sequentially while stirring, dispersing at 1000 rpm for 5 minutes. Add components 6-14 sequentially while stirring, dispersing at 1000 rpm for 10 minutes. Then add zirconium beads and grind at high speed until the fineness is less than 25 microns. Filter and set aside to obtain component A. Accurately weigh components 15 and 16, mix and stir evenly, and filter to obtain component B. Mix components A and B at a mass ratio of 100:32, stir evenly, and filter to obtain an aramid fiber composite modified waterborne epoxy coating.
[0067] Example 4
[0068] Preparation of emulsifiers:
[0069] Weigh out 2 parts of E51 epoxy resin, 1 part of 4000 molecular weight polyethylene glycol, 0.5 parts of 4000 molecular weight polyetheramine, and 0.01 parts of tetrafluoroboric acid; add E51 epoxy resin and polyethylene glycol to a reactor, heat to 100℃, add all the tetrafluoroboric acid dropwise over 1 hour, keep the reaction at 100℃ for 3 hours, add polyetheramine, heat to 120℃, and continue the reaction for 4 hours to obtain a nonionic emulsifier for polyetheramine grafted modified epoxy resin.
[0070] Preparation of aramid fiber modified epoxy emulsion:
[0071]
[0072]
[0073] (1) Weigh 8 parts of aramid fiber, 50 parts of water, and 0.8 parts of dispersant by weight, turn on the cooling water, and disperse at 3000 r / min for 4 h at 25℃ to obtain a well dispersed aqueous solution of aramid fiber, wherein the aramid fiber is para-aramid fiber.
[0074] (2) By weight, add 40 parts of E20 epoxy resin, 5 parts of emulsifier and 8 parts of cosolvent to the jacketed reactor. After heating to melt at 80°C, start the dispersion and stir evenly at 1500 r / min. Keep the material temperature at 60°C. Start the peristaltic pump and add 60 parts of aramid fiber aqueous solution at a rate of 2 ml / min. After the addition is complete, stir at 1500 r / min for 30 min. After filtration, the aramid fiber modified epoxy emulsion is obtained.
[0075] Preparation of aramid fiber composite modified waterborne epoxy coatings:
[0076] The amounts of each component by weight are shown in the table below. Accurately weigh component 1 and add it to the dispersion tank. Add components 2-5 sequentially while stirring, dispersing at 1000 rpm for 5 minutes. Add components 6-14 sequentially while stirring, dispersing at 1000 rpm for 10 minutes. Then add zirconium beads and grind at high speed until the fineness is less than 25 microns. Filter and set aside to obtain component A. Accurately weigh components 15 and 16, mix and stir evenly, and filter to obtain component B. Mix components A and B at a mass ratio of 100:32, stir evenly, and filter to obtain an aramid fiber composite modified waterborne epoxy coating.
[0077]
[0078]
[0079] Comparative Example 1
[0080] The difference from Example 2 is that no aramid fiber was added; the rest of the composition and preparation process are exactly the same.
[0081] Performance testing
[0082] Adhesion was determined by cross-cut adhesion test according to GB / T 9286-2021;
[0083] The water resistance of the paint film was tested in accordance with GB / T 1733-1993;
[0084] The salt spray resistance of the paint film was determined in accordance with GB / T 1771-2007;
[0085] The impact resistance of the paint film was determined in accordance with GB / T 1732-1993;
[0086] The hardness of the paint film was determined in accordance with GB / T 6739-2006.
[0087] Table 1 shows the experimental data for different implementation schemes.
[0088] The test results are shown in Table 1 below:
[0089] Appearance Flat and smooth Flat and smooth Flat and smooth Surface wrinkles Flat and smooth Adhesion Level 0 Level 0 Level 0 Level 0-1 Level 0 Water resistance 10 days 15 days 15 days 3 days 7 days Salt spray resistance 400h 800h 776h 344h 320h Impact resistance >50cm >60cm >60cm >40cm >50cm hardness H 2H 2H HB HB
[0090] As shown in the table above, the comparison between the examples and comparative examples demonstrates that the technical solution of this invention effectively disperses aramid fibers in waterborne epoxy emulsions, preventing agglomeration. In Example 2, the waterborne epoxy coating modified with aramid fibers exhibits water resistance ≥15 days, salt spray resistance ≥800 hours, and impact resistance >60 cm, all superior to Comparative Example 1. This is because aramid fibers, as a reinforcing material, can fill pinholes and defects that appear after the coating solidifies due to moisture evaporation, shielding it from corrosive media. Furthermore, the multi-layered coating of aramid fibers requires a longer time for external corrosive media to penetrate the protective film, increasing the difficulty of the corrosive liquid penetrating the metal substrate surface. However, as the amount of aramid fibers gradually increases, wrinkles appear in the coating's appearance, and adhesion and salt spray resistance also decrease. This is because when the addition amount is too high, excessive aramid fibers are difficult to disperse, and the excess aramid fibers remain outside the system, causing some damage to the coating's performance.
[0091] As shown in the figure, Figure 2 The emulsifier spectrum of polyetheramine grafted modified epoxy resin shows the characteristic peak of the epoxy group at 830 cm⁻¹. -1 and 915cm -1 It also retains epoxy groups, exhibiting good compatibility with epoxy resins. During the later stages of emulsion curing and film formation, it can participate in the curing process, increasing the crosslinking density of the coating. The NH peak in polyetheramine is 3312 cm⁻¹. -1 The absence of the substance indicates that the reaction is complete and has no impact on the stability during subsequent storage.
[0092] The descriptions of the above embodiments are merely illustrative of the methods and core ideas of the present invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Therefore, the present invention is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. An aramid fiber composite modified waterborne epoxy coating, characterized in that, Its raw material composition includes two components, A and B. Component A, by weight, includes 40-60 parts of aramid fiber modified epoxy emulsion, 10-70 parts of pigments and fillers, 0.1-3 parts of flash rust inhibitor, 0.1-5 parts of dispersant, 2-3 parts of film-forming aid, 1-3 parts of defoamer, 1-3 parts of thickener, 1-2 parts of wetting agent, and 10-50 parts of water. Component B, by weight, includes 10-40 parts of curing agent and 5-20 parts of propylene glycol methyl ether. The mass ratio of components A and B is 100:30-40. The aramid fiber-modified epoxy emulsion was prepared according to the following method: (1) Add 1-10 parts of aramid fiber, 0.1-1 parts of dispersant, and 50-90 parts of water to the jacketed reactor, turn on the condenser, and disperse at 25°C and 2000-4500 r / min for 2-6 h to obtain a well dispersed aramid fiber aqueous solution. (2) Add 40-60 parts of epoxy resin, 4-8 parts of emulsifier, and 6-12 parts of cosolvent to the jacketed reactor. Heat at 60-80℃ until melted, then start the dispersion and stir at 1000-2000r / min until uniform. Keep the material temperature at 60-65℃, turn on the peristaltic pump, and add 30-60 parts of aramid fiber aqueous solution at a rate of 1-2ml / min. After the addition is complete, stir at 1000-1500r / min for 15-30min. After filtration, obtain aramid fiber modified epoxy emulsion. The aramid fiber is a para-aramid fiber with a diameter between 10-100 nm. The emulsifier is a nonionic emulsifier of polyetheramine grafted modified epoxy resin, and the preparation method is as follows: Weigh out 2-5 parts by weight of E51 epoxy resin, 1-5 parts by weight of polyethylene glycol with a molecular weight of 3500-6000, 0.5-2 parts by weight of polyetheramine with a molecular weight of 2000-4000, and 0.01-0.03 parts by weight of tetrafluoroboric acid. Add the E51 epoxy resin and polyethylene glycol to the reactor, heat to 100-110℃, add all the tetrafluoroboric acid dropwise over 1-2 hours, keep the reaction at 100-110℃ for 3-4 hours, add the polyetheramine, heat to 120-140℃, and continue the reaction for 4-6 hours to obtain a nonionic emulsifier for polyetheramine grafted modified epoxy resin.
2. The aramid fiber composite modified waterborne epoxy coating according to claim 1, characterized in that, The epoxy resin is selected from bisphenol A type epoxy resin.
3. The aramid fiber composite modified waterborne epoxy coating according to claim 1, characterized in that, The epoxy resin is selected from one or more of E51, E44, and E20 epoxy resins.
4. The aramid fiber composite modified waterborne epoxy coating according to claim 1, characterized in that, The co-solvent is selected from one or more of propylene glycol methyl ether, propylene glycol butyl ether, and acetone; The pigments and fillers are selected from one or more of titanium dioxide, talc, barium sulfate, iron oxide red, zinc phosphate, strontium chrome yellow, and mica powder; The dispersant is selected from one or more of dodecyl sulfonates, alkyl alcohol polyoxyethylene ethers, polyacrylates, and polycarboxylates; The film-forming aid is selected from one or more of dipropylene glycol methyl ether, propylene glycol methyl ether, and dipropylene glycol butyl ether; The defoamer is selected from one or more of polyether block derivatives, organosilicon derivatives, and mineral oil derivatives; The thickener is selected from one or more of cellulose-based, polyacrylic acid-based, inorganic thickeners, and polyurethane-based thickeners; The curing agent is selected from one or more of Huntsman 3986, Hansen 6870, and Zhanxin 613W.
5. The aramid fiber composite modified waterborne epoxy coating according to claim 1, characterized in that, The flash rust inhibitor is one or more of CK-20, CK-35, and HY-72; the wetting agent is one or more of TEGO-245, TEGO-270, and TEGO280.
6. The preparation method of the aramid fiber composite modified waterborne epoxy coating according to claim 1, characterized in that, The specific steps include: S1: Preparation of component A: Add aramid fiber modified epoxy emulsion, pigments and fillers, anti-flash rust agent, dispersant, film-forming aid, defoamer, thickener, wetting agent and water to the reactor according to the formula, grind until the fineness is less than 25μm, filter and discharge to obtain component A; S2: Preparation of component B: Add curing agent and propylene glycol methyl ether to the reactor according to the formula, stir and mix evenly at a speed of 500-1000 rpm / min, filter and discharge to obtain component B; S3: Mix component A and component B at a mass ratio of 100:30-40, stir until homogeneous, and filter to obtain a waterborne epoxy coating modified with aramid fiber composite.
Citation Information
Patent Citations
Method of using block polyether to prepare epoxy emulsion
CN101585922A
Aramid nano-fiber corrosion-resistant environmentally-friendly coating material and preparation method thereof
CN106336775A
Waterborne fluorocarbon insulation paint modified by aramid fibers and preparation method thereof
CN109401462A